Gender Gaps in Patience, Risk-Taking, Trust, and Prosociality Have Declined Across Birth Cohorts - Rainer Kotschy; Uwe Sunde (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Men and women differ systematically in measures of patience, risk-taking, trust, and prosociality. While literature documents such gender gaps in numerous countries throughout the world, recent work suggests an association between these gender gaps and economic development, based on evidence of larger gender gaps in Western, educated, industrialized, rich, and democratic societies. However, little is known about how these gender gaps evolve and whether they indeed widen as countries develop. To examine this question, we analyze how within-country gender gaps in patience, risk-taking, trust, and prosociality have evolved across birth cohorts worldwide. We compare these gender gaps across country-period-cohort cells using two survey data sets that cover 460,000 people in more than 100 countries. Our results document that gender gaps in patience, risk-taking, trust, and prosociality have declined across birth cohorts. This evidence rejects the notion that these gender gaps widen as countries develop and instead points to a decline in socioeconomic differences between men and women.
Keywords: D01; J10; J11; 330; preferences; personality traits; gender gaps; cohort trends